MRI characterization of hemodynamic patterns of human fetuses with cyanotic congenital heart disease. (1st December 2021) - Sun, L.; van Amerom, J. F. P.; Marini, D.; Portnoy, S.; Lee, F.‐T.; Saini, B. S.; Lim, J. M.; Aguet, J.; Jaeggi, E.; Kingdom, J. C.; Macgowan, C. K.; Miller, S. P.; et al.
ABSTRACT: Objectives: To characterize, using magnetic resonance imaging (MRI), the distribution of blood flow and oxygen transport in human fetuses with subtypes of congenital heart disease (CHD) that present with neonatal cyanosis. Methods: Blood flow was measured in the major vessels of 152 late‐gestation human fetuses with CHD and 40 gestational‐age‐matched normal fetuses, using cine phase‐contrast MRI. Oxygen saturation (SaO2 ) was measured in the major vessels of 57 fetuses with CHD and 40 controls. Results: Compared with controls, we found lower combined ventricular output in fetuses with single‐ventricle physiology, with the lowest being observed in fetuses with severe forms of Ebstein's anomaly. Obstructive lesions of the left or right heart were associated with increased flow across the contralateral side. Pulmonary blood flow was reduced in fetuses with Ebstein's anomaly, while those with Ebstein's anomaly and tricuspid atresia had reduced umbilical flow. Flow in the superior vena cava was elevated in fetuses with transposition of the great arteries, normal in fetuses with hypoplastic left heart, tetralogy of Fallot or tricuspid atresia and reduced in fetuses with Ebstein's anomaly. Umbilical vein SaO2 was reduced in fetuses with hypoplastic left heart or tetralogy of Fallot. Ascending aorta and superior vena cava SaO2 were reduced in nearly all CHD subtypes. Conclusions: Fetuses with cyanotic CHD exhibit profound changes in the distribution of blood flow and oxygen transport, which result in changes in cerebral, pulmonary and placental blood flow and oxygenation. These alterations of fetal circulatory physiology may influence the neonatal course and help account for abnormalities of prenatal growth and development that have been described in newborns with cyanotic CHD. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.